Inuit adaptability to changing environmental conditions over an 11-year period in Ulukhaktok, Northwest Territories. (19th June 2018) - Fawcett, David; Pearce, Tristan; Notaina, Roland; Ford, James D.; Collings, Peter
ABSTRACT: Current understanding of climate change impacts, adaptation and vulnerability among Inuit in the Arctic is relatively static, rooted in the community and time that case studies were conducted. This paper captures the dynamism of Inuit–climate relationships by applying a longitudinal approach to assessing vulnerability to climate change among Inuit in Ulukhaktok, Northwest Territories, Canada. Data were collected in 2005 and 2016 following a consistent methodology and analytical framework. Findings from the studies are analysed comparatively together with longitudinal datasets. The data reveal that many of the climatic changes recorded in 2005 that adversely affected hunting activities have been observed to be persisting or progressing, such as decreasing sea ice thickness and extent, and stronger and more consistent summer winds. Inuit are responding by altering travel routes and equipment, taking greater pre-trip precautions, and concentrating their efforts on more efficient and accessible hunts. Increasing living and subsistence costs and time-constraints, changes in the generation and transmission of environmental knowledge and land skills, and the concentration of country food sharing networks were identified as key constraints to adaptation. The findings indicate that the connections between subsistence activities and the wage economy are central to understanding how Inuit experience and respond to climate change.